Legume Genetics and Biology: From Mendel's Pea to Legume Genomics - Smýkal, Petr; von Wettberg, Eric J B; McPhee, Kevin (International journal of molecular sciences, 2020)
Legumes have played an important part in cropping systems since the dawn of agriculture, both as human food and as animal feed. The legume family is arguably one of the most abundantly domesticated crop plant families. Their ability to symbiotically fix nitrogen and improve soil fertility has been rewarded since antiquity and makes them a key protein source. The pea was the original model organism used in Mendel's discovery of the laws of inheritance, making it the foundation of modern plant genetics. This Special Issue provides up-to-date information on legume biology, genetic advances, and the legacy of Mendel.
Keywords: proteins; dějiny 19. století; Humans; Fabaceae; Nitrogen Fixation; History, 19th Century; History, Medieval; genomics; genomika; legumes; Phenotype; lidé; dějiny starověku; genetická variace; nitrogen fixation; Genetic Variation; Crops, Agricultural; modely genetické; fenotyp; History, Ancient; Heredity; Models, Genetic; dědičnost; Genomics; fixace dusíku; zemědělské plodiny; dějiny středověku